Catalytic methanation reaction over supported nickel-ruthenium oxide base for purification of simulated natural gas - Wan Abu Bakar, Wan Azelee (Sharif University of Technology, 2012)
The presence of carbon dioxide and water molecules as impurities in crude natural gas decreases the quality of natural gas. Recently, the catalytic treatment of this toxic and acidic gas has become a promising technique by converting CO2 to methane gas in the presence of H2S gas; thus, enhancing methane production and creating an environmentally friendly approach to the purification of natural gas. A series of catalysts based on nickel oxide were prepared using the wetness impregnation technique and aging, followed by calcination at 400 °C. Pd/Ru/Ni(2:8:90)/ Al2O3 catalyst was revealed as the most potential catalyst, and achieved 43.60% of CO2 conversion, with 6.82% of methane formation at 200 °C. This catalyst had the highest percentage of 52.95% CO2 conversion and yielded 39.73% methane at a maximum temperature of 400 °C. In the presence of H2S in the gas stream, the conversion dropped to 35.03%, with 3.64% yield of methane at a reaction temperature of 400 °C. However, this catalyst achieved 100% H2S desulfurization at 140 °C and remained constant until the reaction temperature of 300 °C. Moreover, the XRD diffractogram showed that the catalyst is highly amorphous in structure, with a BET surface area in the range of 220-270 m2 g- 1. FESEM analysis indicated a rough surface morphology and non-homogeneous spherical shape, with the smallest particles size in the range 40-115 nm.